The Success of Endodontic Treatments Performed by Dental Residents in Advanced Education in General Dentistry Program: A 10-Year Retrospective Study - Nisreen Al Jallad; Eli Sun; Tongtong Wu; Shasha Cui; Amer Basmaji; Radhika Thakkar; Shahenda Aboelmagd; Neha Naik; Konstantina Tzouma; Jin Xiao; Hans Malmstrom (Dentistry Journal, 2025)
Objectives: This study aimed to evaluate the success rates of NSRCT performed by AEGD residents and to identify predictive factors associated with clinical outcomes and patient satisfaction. Methods: A retrospective chart review was conducted on cases treated between 2012 and 2021. Eligible cases included fully developed permanent teeth that underwent NSRCT and received a final restoration by general dentistry residents, with a minimum of 12 months of follow-up. Data collected included demographic information, medical history, clinical symptoms, radiographic findings, instrumentation, type and timing of final restorations, and patient satisfaction scores. Treatment success was defined as the absence of symptoms and either the resolution or stability of periapical radiolucency. Patient satisfaction and pain levels were also analyzed. Results: AEGD residents achieved radiographic and clinical RCT success rates of 93.3% and 91.5%, respectively. Multivariate logistic regression showed that the presence of an intact restoration was significantly associated with increased odds of tooth retention (odds ratio [OR] = 3.4, p < 0.001), while post placement in a straight root was also a significant predictor of survival (OR = 4.2, p = 0.02). Conversely, pre-existing radiolucency (OR = 0.37, p = 0.018) and the use of a metal post (OR = 0.23, p = 0.012) were significantly associated with lower odds of tooth retention. Worse periodontal health was significantly associated with increased odds of pain on percussion, with a 74.19% increase in odds per worsening category (OR = 1.74, p = 0.002). Patient satisfaction was significantly higher when restorations remained intact, with esthetic satisfaction increasing by a factor of 3.08 (OR = 3.08, p < 0.001) and functional satisfaction increasing by a factor of 3.9 (OR = 3.9, p < 0.001). Conclusions: Endodontic treatments performed by AEGD residents demonstrated high success rates and favorable patient-reported outcomes. Restoration integrity, periodontal health, and post and final restoration selection play critical roles in treatment success and patient satisfaction.